The Role of Regional Expenditure in Mitigating Poverty: A Regional Economic Perspective of East Java - Rahmadany, Achmad Fauzan; Sulistyono, Setyo Wahyu (International Journal of Economics Development Research (IJEDR), 2024)
Poverty is a multidimensional issue that reflects the inability of individuals or groups to meet basic needs such as food, education, and healthcare. In East Java, the Covid-19 pandemic exacerbated poverty conditions, significantly increasing unemployment rates and widening disparities between urban and rural areas. This study aims to analyze the impact of Regional Original Revenue (ROR), regional expenditures, labor force participation, and population size on poverty levels in East Java from 2018 to 2022. Using a quantitative method with a panel data approach, the study covers 38 districts/cities. Secondary data were obtained from the Central Statistics Agency (CSA) and analyzed using the Fixed Effect Model. The findings reveal that Regional Original Revenue (ROR) does not have a significant effect on poverty levels in East Java. Conversely, regional expenditures and the labor force significantly impact poverty; regional expenditures effectively reduce poverty levels, while the labor force, when not accompanied by job creation, contributes to an increase in poverty. Meanwhile, population size does not show a significant effect on poverty. However, simultaneously, ROR, regional expenditures, labor force, and population size significantly influence poverty levels. Therefore, poverty alleviation in East Java requires integrated policies that include optimizing ROR allocation, improving the efficiency of regional expenditures, creating adequate job opportunities, and managing population growth through education and training. These measures are expected to deliver sustainable long-term impacts.